PENGARUH MEDIA TANAM DAN NUTRISI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCHOI (Brassica juncea L.) DENGAN SISTEM HIDROPONIK - Balia Perwitasari; Mustika Tripatmasari; Catur Wasonowati (Agrovigor, 2012)
Pakchoi (Brassica juncea L.). is one kind of a vegetable crop that has high economic value and high nutrition. The technology of hydroponic is one of alternative cultivation using other media than soil substrates and nutrients. The purpose of this research is to determine the effect of media composition and nutrition on growth and yield of  pakchoi crops and find out which treatment is best for plant growth and yield of pakchoi. Researchcarried outinthe gardenexperiment ina plastichouse, Faculty ofAgriculture, University ofTrunojoyoMadura, at an altitude of±5 mabove sea level, temperature29ºC, and± 75% RH. The research was conductedin December2011 toFebruary2012.The analysis was usednonfaktorialRAL. Treatmentwithcomposemediatypes(raw rice husk, rice huskcharcoal, sand) andnutrients(no nutrients, premiumnutrition, nutritiongoodplant). There are ninetreatment, threereplicationsandthreesamples ofthe plant, furthertestswere analyzed byDMRT5%. Results showedthe treatmentcompositionandnutrientmediaprovidesignificantly differentresultsatdifferent ages ofobservationson eachvariableobservation. The besttreatmentcompositioncontained in thehusk charcoalandnutrientmediagoodplant(M2N2). Evidenced by theaverage ofthe highestresultson the length ofthe plant(29.38cm), number of leaves(22.22 strands), leaf area(3226.79 cm2), wetweight(242.19 g) and dry weight(13, 27g) totalplantpakchoiat age4 MST.